Lysosome-associated CASM: from upstream triggers to downstream effector mechanisms - Kaur, Namrita; Carlsson, Sven R.; Lystad, Alf Håkon (Frontiers in Cell and Developmental Biology, 2025)
Lysosomes are dynamic organelles critical for cellular degradation and signaling, safeguarded by a limiting membrane that prevents leakage of harmful contents into the cytoplasm. Upon lysosomal damage, cells deploy defensive mechanisms, including a key process called CASM (conjugation of ATG8 to single membranes), which lipidates ATG8 proteins onto the limiting membrane to support protective pathways. CASM operates through two pathways: VAIL, induced by lysosomal pH changes via V-ATPase and ATG16L1, and STIL, triggered by sphingomyelin exposure and mediated by TECPR1. This review examines CASM’s role in lysosomal damage responses, exploring the mechanisms of damaging agents, distinctions between VAIL and STIL, and the downstream effects of decorating lysosomes with ATG8, including effector recruitment for membrane repair or removal.